Comparison of Retroperitoneal & Transperitoneal Laparoscopic Nephrectomy in Management of Pyonephrosis in Terms of Conversion to Open Surgery - B. Belim, Osman; Shah, N J; V Patil, Milind; Pasi, Bodhraj (International Journal of Medical Research and Review, 2014)
Introduction: Since the mid-1990s, there has been an evolution in surgical practice from traditional open approaches to minimally invasive means of treating operative lesions. This study is carried out to study rate & indication of conversion to open surgery in pyonephrosis using retroperitonel and trans peritoneal laproscopic nephrectomy. Materials And Methods: This study was retrospective study done in Department of Urology Civil hospital & B J Medical College Ahmadabad .We performed a retrospective review of a maintained database of 219 consecutive laparoscopic simple nephrectomies done for pyonephrosis between July 2001 to February. 2013. Results: In study transperitoneal route using four ports was used in 165 (75.3%) while retroperitoneal access using three was used in 54(24.6%) patients. In our study total 163 (74.4%) had PCN (percutaneous nephrostomy) in situ, 79.3% in lap transperitoneal group and 59.2% in lap retro peritoneal group. 27(12.3%) patients required conversion to open surgery. Adhesion 13(5.9%) and bleeding 9(4.1%) were the main factors for conversion, while 2 (0.9%) patients required conversion due to bowel injury and limited space in 3(1.3%) patients. Conversion rate was 12.1 % (20/165) for transperitoneal procedures while 12.9 % (7/54) for retroperitoneal approach. Laparoscopic approach requires proper placement of ports for meticulous surgical dissection. Preoperative plain and CECT help in identifying renal hilar anatomy as well as the relationship with the surrounding structures. Conclusion: In our study, retroperitoneal laparoscopic nephrectomy has to be considered equal to transperitoneal laproscopic nephrectomy in terms of conversion to open surgery.